Turkey’s violations of Article 3 of the European Convention on Human Rights in closed institutions - Karu, Karīna (Riga Graduate School of Law, 2021)
Turkey has always been condemned by the international community for its anti-democratic ways of handling detained persons in their closed institutions that causes severe human rights violations as detained persons are particularly vulnerable and unprotected against various forms of ill-treatment by law enforcement officials. This thesis will specifically concentrate on Turkey’s violations of Article 3 of the European Convention on Human Rights (ECHR) in closed institutions. In order to comprehend what are the reasons for Turkey to breach Article 3, different academic resources, cases, reports, and other official documents, were perused thoroughly to discover the crucial information. By doing this research it was discovered that Turkey violates Article 3 for political reasons to get the opposition party under control, to gain information about crimes, and to satisfy their barbaric needs, however, there are no specific reasons when it comes to foreigners and special needs detainees.
Keywords: Human rights; Turkey